Genetic variants in SLC22A3 contribute to the susceptibility to colorectal cancer. Issue 1 (3rd January 2019) - Ren, Anjing; Sun, Shanwen; Li, Shuwei; Chen, Tao; Shu, Yongqian; Du, Mulong; Zhu, Lingjun
Abstract : Previous a genome‐wide association study (GWAS) of colorectal cancer in Japanese population has identified a risk region at the chromosome 6q26‐q27 associated with colorectal cancer risk. However, the causal gene at this locus remained unclear. In our study, we enrolled a total of 14 candidate functional single nucleotide polymorphisms (SNPs) at 6q26‐q27 (318 kb), and then genotyped them by TaqMan method in a Chinese population including 1, 147 colorectal cancer cases and 1, 203 controls. Among that, 5 SNPs were identified statistical association with colorectal cancer risk by logistic regression analysis. Of which, SNP rs420038 G > A in SLC22A3 was related to decreased risk of colorectal cancer (adjusted odds ratio (OR) = 0.79, 95% confidence interval (CI) = 0.67–0.94, p = 0.007), and also associated with lower expression of SLC22A3 ( p = 0.040) using expression quantitative trait loci (eQTL) analysis. Moreover, by the luciferase assays, we found that compared to the G allele of rs420038, the A allele could suppress the activity of the promoter in SLC22A3 . Furthermore, the expression of SLC22A3 was significantly higher in colorectal cancer tissues than that in paired normal tissues ( p < 0.001). Meanwhile, the phenotypes of proliferation, migration, invasion, cell cycle and apoptosis of colorectal cancer cell were significantly affected by SLC22A3 in vitro . Our results revealed a novel susceptible locus, rs420038 in SLC22A3, which may be involved in colorectal cancer development and progression. Abstract : What's new? The identification of genes or loci associated with colorectal cancer (CRC) susceptibility can facilitate the discovery of molecular pathways underlying CRC development and progression. Here, the authors investigated a risk region at chromosome 6q26‐q27, which previously was linked to CRC susceptibility in a Japanese population. Analyses of candidate functional single nucleotide polymorphisms (SNPs) at 6q26‐q27 revealed a novel functional SNP, rs420038 G>A, in the SLC22A3 gene. While expression of SLC22A3 was elevated in CRC tissues, the novel SNP was associated with decreased CRC risk in a Chinese population. The A allele of rs420038 significantly suppressed SLC22A3 promoter activity.